Partial lateral internal sphincterectomy vs. manual anal dilatation in the treatment of anal fissures.: Prospective and randomized study. - Estefan, Alberto; Carriquiry, Guillermo; Colet, Andrés; Domínguez, Juan; Grezzi, Roberto (Cirugía del Uruguay, 1985)
The authors make a prospeclive and randomized study inlended to evaluate !he parlial interna! sphincterectomy and the manual anal dilatalion in the treatment of anal fissure.